Analisis Modal Kerja Terhadap Tingkat Profitabilitas Pada PT. Gaya Makmur Tractors Makassar - Pra Gemini; Fausiah Fausiah; Anggraeni Anggraeni (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Analysis of Working Capital on Profitability Levels at PT. Gaya Makmur Tractors Makassar, Thesis for the Management Study Program at the Indonesian Educational Institute of Management Science College (STIM-LPI) Makassar. (supervised by Dra. Pra Gemini, M.Si and Fausiah, S.E., M.Si). This research aims to determine how working capital influences the level of profitability at PT. Gaya Makmur Tractors Makassar. The type of research used in this research is quantitative. The data processed is the financial report of PT. Gaya Makmur Tractors Makassar for 2019-2021 which consists of a profit and loss report and balance sheet. The research results of the current ratio are stated to be good because they continue to increase every year 2019-2021 and exceed the internal average standard in 2020 and 2021. On the activity ratio with measurements using the NWC Turnover ratio can be said to be quite good because it exceeds the internal average, although it experienced a decline in 2020 of 368% but rose again to 430% in 2021. The profitability ratio with Return On Investment is said to be not good because it is below the internal average . Return on Equity is said to be not good, although it has increased in 2019 and 2021, this ratio is still below the internal average. Gross Profit Margin is also still said to be not good or not optimal because it experienced ups and downs from 2019-2021, namely 173%, 181%, 175%, although in 2020 it experienced an increase and was above the internal average of 176.3% but in 2021 experienced another decline and was below the internal average. Net Profit Margin is also said to be not good because it is still below the internal average.